PENGARUH VARIASI TEMPERATUR PENUANGAN Al-Si / Al2O3 TERHADAP SIFAT MEKANIK DAN STRUKTUR MIKRO MATERIAL SEPATU REM MENGGUNAKAN PENGECORAN HPDC - Kusumaning R. Putri; Athanasius Priharyoto Bayuseno (JURNAL TEKNIK MESIN, 2013)
In this research, the raw material used Al-Si is a product of PT. Pinjaya Metals, Mojokerto. HPDC performed at a constant pressure of 7 MPa and variation of pouring temperature at 700°C, 750oC, and 800oC. The heat treatment process used is age hardening with solution treatment at 490oC for 15 minutes, then artificial aging at 150oC for 4 hours.  Porosity test performed using the Archimedes law that use mass of wet and dry specimen. Hardness test using Rockwell method with the scale of B, and test the microstructure using an optical microscope with a magnification of 1000X. The results of porosity test show that the density at pouring temperature 700°C is 1,613 g/cm3, at 750oC is 1,642 g/cm3, and at 800oC is 1,622 g/cm3. On the hardness testing increased hardness values was obtained at pouring temperature 700°C is 38 HRB. While at pouring temperature 750oC is 43,67 HRB and 800oC is 46,06 HRB. On themicrostucture, at pouring temperature 750oC and 800oC shows that the value of the grain size is lower than the size of a grain of pouring temperature on 700oC. Further results on testing was able to show that there is value in flow ability that the higher when the temperature increasing in 700°C is 580,67 mm, 750°C is 682,33 mm and then 800°C is 965,33 mm.